2021
DOI: 10.55563/clinexprheumatol/73txen
|View full text |Cite
|
Sign up to set email alerts
|

The ovarian reserve as measured by the anti-Müllerian hormone is not diminished in patients with rheumatoid arthritis compared to the healthy population

Abstract: ObjectiveRheumatoid arthritis (RA) is the most prevalent chronic inflammatory arthritis, affecting 0.5-1% worldwide population and predominates in females. Altered fertility has been reported due to a decrease in ovarian reserve secondary to sustained inflammation. The anti-Müllerian Hormone (AMH) is currently the most reliable biomarker of ovarian reserve.However, few and contradictory studies have been reported to analyse the relationship between fertility in RA female patients and AMH. The aim of present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…A previous study demonstrated that the AMH level was lower in the RA group, but there was no significance of AMH levels in the activity rheumatoid arthritis, rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP), erosions, C-reactive protein (CRP) level or therapeutic schedule [ 113 ]. Another study reported a similar result, but found a negative correlation between the levels of AMH and IL-10 [ 114 ]. Therefore, we suggest that the decrease in AMH levels in RA patients may not be caused by RF but may be related to a more common inflammatory factor caused by RA, and IL-10 is one of the possibilities (Fig.…”
Section: Hormonal Influence On Ovarian Reservementioning
confidence: 55%
“…A previous study demonstrated that the AMH level was lower in the RA group, but there was no significance of AMH levels in the activity rheumatoid arthritis, rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP), erosions, C-reactive protein (CRP) level or therapeutic schedule [ 113 ]. Another study reported a similar result, but found a negative correlation between the levels of AMH and IL-10 [ 114 ]. Therefore, we suggest that the decrease in AMH levels in RA patients may not be caused by RF but may be related to a more common inflammatory factor caused by RA, and IL-10 is one of the possibilities (Fig.…”
Section: Hormonal Influence On Ovarian Reservementioning
confidence: 55%
“…A metaanalysis conducted by Zhang et al showed that RA patients tended to have ovarian failure [21]. Conversely, another study showed no difference in ovarian reserve between RA patients and healthy controls [22].…”
Section: Premature Ovarian Insufficiency In Autoimmune Diseasesmentioning
confidence: 97%
“…Rheumatoid arthritis (RA) is another chronic inflammatory autoimmune disease that often occurs in women of childbearing age. [ 35 ] Although a few studies failed to find impairment in AMH levels in RA women, [ 18 , 36 ] in other studies, AMH levels were reduced [ 19 , 20 ] and showed a more pronounced decline over time in RA women, [ 35 ] suggesting that RA could cause impaired ovarian function.…”
Section: Autoimmunity and Ovarian Reservementioning
confidence: 99%
“…[8] According to reports, autoimmune oophoritis is related to various steroidogenic enzymes antigens, such as 17α-hydroxylase (17αOH), cytochrome P450 side chain cleavage enzyme (P450scc), 21-hydroxylase (21OH), and 3β-hydroxysteroid dehydrogenase (3β-HSD). [50,57] Both 17αOH and [9] AITD (mean ± SD) 167 1.16 ± 0.17* 1.28 ± 0.25 Magri et al (2015) [10] AITD (median (range)) 288 1.40 (1.0-1.7)* 2.27 (1.7-2.3) Özalp Akın et al (2018) [11] Hashimoto's thyroiditis (adolescents) (median (range)) 60 1.7 (0.5-5.1) 1.8 (0.29-5.5) Pirgon et al (2016) [12] Hashimoto's thyroiditis (adolescents) (mean ± SD) 60 10.6 ± 10.4* 7.5 ± 7.3 Tuten et al (2014) [13] Hashimoto's thyroiditis (median (range)) 81 4.82 (1.47-7.38)* 2.44 (1.63-3.29) Ma et al (2013) [14] SLE (mean ± SD) 44 1.71 ± 1.29* 3.33 ± 1.76 Malheiro et al (2014) [15] SLE (median (range)) 54 1.23 (0.24-4.63) 1.52 (1.33-1.88) Soto (2009) et al [16] T1DM (mean ± SD) 124 12.1 ± 9.2 (pmol/L) 14.2 ± 10.8 (pmol/L) Kadiroğulları et al (2020) [17] T1DM (mean ± SD) 107 2.10 ± 1.23 (pmol/L)* 3.05 ± 1.89 (pmol/L) Lopez-Corbeto et al (2020) [18] RA (median (range)) 119 1.27 (0.42-2.24) 1.31 (0.46-3.09) Henes et al (2015) [19] RA (median(range)) Unknown 1.8 (0.0-11.3)* 2.4 (0.3-13.2) Brouwer et al (2019) [20] RA (median (range)) Unknown 2.5 (1.54.6) Unclear Aydogan Mathyk et al (2019) [21] Psoriasis (mean ± SD) 72 1.85 ± 1.13* 2.46 ± 1.21 de Souza et al (2015) [22] Dermatomyositis (n (%)) 39 ≤1: 8 (50%)* ≤1: 3 (13%) Yalçın Bahat et al (2021) [23] Ankylosing spondylitis (mean ± SD) 104 1.188 ± 0.891* 2.203 ± 1.110 Karakus et al (2017) [24] Sjögren's syndrome 49 Unclear Unclear Henes et al (2015) [19] Behçet's disease (median (range)) Unknown 1.1 (0-6.1)* 1.9 (0.1-13.2) Henes et al (2015) [19] Spondyloarthritis (median (range)) Unknown 1.5 (0.1-7.4)* 2.3 (0.05-13.2) Thöne et al (2016) [25] Relapsing-remitting multiple sclerosis (mean ± SD) 134 2.47 ± 0.26* 3.34 ± 0.34 AFC (n)…”
Section: Autoimmune Oophoritis In Poimentioning
confidence: 99%